The relationship of imposter phenomenon, self-esteem, and resilience: promoting well-being among registered nurses - Lizy Sonia Benjamin; Sumathi Robert Shanmugam; Judith Odanee Magwilang; Sahar Mahmoud Abdulla Hashim; Amutha Chellathurai; Asma Saad Habbash; Yahya Showkan Ali Hamdi; Fatimah Abdulla Asiri; Punitha Josephine; Romeo Jr Mostoles; Omar Hamed Matar Alshammari; Sultan Kayed Alharbi (BMC Nursing)
Abstract Introduction Imposter phenomenon (IP) is common among health care professionals. Nursing is highly stressful and IP can manifest in several ways. Much research has been conducted on IP in various professions, but understanding the relationship between IP, self-esteem, and resilience is lacking among registered nurses. This study aimed to determine the relationships between IP, self-esteem, resilience, and well-being in registered nurses, and to investigate the potential mediating role of self-esteem within these pathways. Methods This cross-sectional study involved the 292 registered nurses in Aseer, Saudi Arabia. Data were collected online between March and May 2024 using a self-report questionnaire. The study utilized the Clance Impostor Phenomenon Scale (CIPS), the Rosenberg Self-Esteem Scale (RSE), and Nicholson McBride Resilience Questionnaire (NMRQ) to measure the respective constructs. Descriptive statistics, correlation analysis, multiple regression, and path analysis were used to analysed the data. Results Nurses have moderate IP (Mean = 49.75; SD = 18.02) alongside self-esteem (Mean = 27.53; SD = 2.71) and resilience (Mean = 42.85; SD = 8.38). Moreover, a non-significant correlation (r = − 0.002, p = 0.975) between IP and self-esteem was observed. Conversely, IP does significantly positively correlate with resilience (r = 0.578, p < 0.001). For self-esteem prediction (R² = 0.475), resilience served as a strong positive predictor (β = 0.680, p < 0.001), while IP was not a significant predictor (β=−0.001, p = 0.975). Furthermore, mediation analysis verified strong direct impact of self-esteem on resilience (β = 1.1391, p < 0.001) as well as IP directly impacting resilience (β = 0.2693, p < 0.001). Notably, IP did not mediate the relationship between self-esteem and resilience, showing an indirect effect of (β=−0.0033, 95% CI: -0.1790 to 0.1928). Conclusion Nurses tend to have self-esteem and resilience at a moderate level alongside the IP. Of interest, IP does not directly correlate with self-esteem—this is contrary to many claims. Also notable is that IP and resilience do tend to correlate positively. This indicates that coping mechanisms are likely to be formulated as a response to the feelings of an imposter, whereas self-esteem is predicted by resilience directly without mediation of IP. This strongly supports the need to design targeted interventions to enhance self-esteem and resilience among nurses in order to improve their wellbeing, productivity, and professional engagement.